Faktor-Faktor yang Berhubungan dengan Kejadian Leukorrhea (Keputihan) Pada Remaja Putri Kelas X - Rinda Lamdayani (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
Reproductive health problems, especially the often complained of whitish, not infrequently whitish can interfere to cause discomfort in daily activities. The purpose of this study to determine the factors associated with the incidence of Leukorrhea (leucorrhoea) in teenage girls x high school SMA Ibu Palembang. This research method is Analytical Survey with Cross-Sectional design. The population is all students of SMA KaryaIbu Palembang with 60 respondents. Samples used in Total Sampling. Data analysis using the Chi-Square test. This research was conducted in May 2017. Based on bivariate analysis using Chi-Square test, it is applied by knowledge variable ρ Value = 0,033 <0,05, adolescent age ρ Value = 0,023 <0,05. And attitude ρ Value = 0,046 <0,05. There is a significant relationship with knowledge, age of adolescence, and attitude with the incidence of Leukorrhea (Dish).